2015
DOI: 10.9767/bcrec.10.1.7802.98-103
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and NO-CO Redox Reaction Studies over Palladium and Rhodium Oxides Supported on Manganese Dioxide

Abstract: The catalytic activity of PdO/MnO2 and Rh2O3/MnO2 is investigated for NO-CO redox reaction. Supported catalysts are prepared by wet impregnation method. Among the tested catalysts, PdO/MnO2 shows higher activity for this reaction. Active metal dispersion on MnO2 enhances the selectivity for N2 over N2O in this reaction. The XRD substantiate the formation of MnO2 monophasic phase. SEM images show the formation of elongated particles. TEM images indicate nano-size rod-like morphologies. An increase in the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In situ FTIR of the NO‐CO reaction over Mn‐Cu/Ti and 0.05Ni‐Mn ­ ‐Cu/Ti was performed to understand the surface reaction situation. As shown in Figure , some reactant species of NO and CO, such as linear nitrate (1270 cm −1 ), bridged nitrate (1633 cm −1 ), weak adsorbed NO (1843 cm −1 , 1907 cm −1 ), and Cu + ‐CO or Cu + ‐(CO) 2 (2121 cm −1 ), were detected on the catalyst surface. Also, the intermediate product of N 2 O can be found at 2237 cm −1 and 2343 cm −1 .…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…In situ FTIR of the NO‐CO reaction over Mn‐Cu/Ti and 0.05Ni‐Mn ­ ‐Cu/Ti was performed to understand the surface reaction situation. As shown in Figure , some reactant species of NO and CO, such as linear nitrate (1270 cm −1 ), bridged nitrate (1633 cm −1 ), weak adsorbed NO (1843 cm −1 , 1907 cm −1 ), and Cu + ‐CO or Cu + ‐(CO) 2 (2121 cm −1 ), were detected on the catalyst surface. Also, the intermediate product of N 2 O can be found at 2237 cm −1 and 2343 cm −1 .…”
Section: Resultsmentioning
confidence: 87%
“…Two desorption peaks around 112 and 187 °C were detected in these two catalysts, suggesting that there are two different types of active adsorption sites for CO on the catalyst surface. It has been reported that the peaks at lower and higher temperatures are due to the desorption of CO on Cu + and Mn 4+ , respectively. It should be noted that a TCD detector was used for CO‐TPD analysis; thus, the production of CO 2 cannot be ruled out.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation